Current Status of Autologous Stem Cell Transplantation in Relapsed and Refractory Hodgkin's Lymphoma - Colpo, Anna; Hochberg, Ephraim; Chen, Yi‐Bin (The oncologist (Dayton, Ohio), 2012)
Despite the relatively high long‐term disease‐free survival (DFS) rate for patients with Hodgkin lymphoma (HL) with modern combination chemotherapy or combined modality regimens, ∼20% of patients die from progressive or relapsed disease. The standard treatment for relapsed and primary refractory HL is salvage chemotherapy followed by high‐dose chemotherapy and autologous stem cell transplantation (ASCT), which has shown a 5‐year progression‐free survival rate of ∼50%–60%. Recent developments in a number of diagnostic and therapeutic modalities have begun to improve these results. Functional imaging, refinement of clinical prognostic factors, and development of novel biomarkers have improved the predictive algorithms, allowing better patient selection and timing for ASCT. In addition, these algorithms have begun to identify a group of patients who are candidates for more aggressive treatment beyond standard ASCT. Novel salvage regimens may potentially improve the rate of complete remission prior to ASCT, and the use of maintenance therapy after ASCT has become a subject of current investigation. We present a summary of developments in each of these areas. 摘要 霍奇金淋巴瘤（ HL ）患者采用现代联合化疗或综合治疗方案后，长期无病生存（ DFS ）率相对较高，但仍有约20%的患者死于疾病进展或复发。复发和原发难治 HL 的标准治疗是解救化疗继以大剂量化疗和自体干细胞移植（ ASCT ），其5年无进展生存率介于约50%~60%。最近开发的若干诊断和治疗方法已开始改善上述结果。功能成像、临床预后因素的细化、新型生物标记物的开发已改进了预测规程，可更好地甄选患者和确定 ASCT 的时机。此外，这些规程已开始检出适于标准 ASCT 之外更具侵袭性治疗的患者。新型解救方案有望提高 ASCT 之前的完全缓解率，ASCT后维持治疗的应用已成为目前研究的课题。本文总结上述各领域的进展。 New developments in the treatment of patients with relapsed/refractory Hodgkin's lymphoma undergoing autologous stem cell transplantation are summarized including modern prognostic markers, the role of functional imaging, the role of newer drugs, different conditioning regimens, and maintenance therapy.